2022
DOI: 10.3390/ph15050552
|View full text |Cite
|
Sign up to set email alerts
|

Galactosylated Prodrugs: A Strategy to Improve the Profile of Nonsteroidal Anti-Inflammatory Drugs

Abstract: Carbohydrates are one of the most abundant and important classes of biomolecules. The variety in their structures makes them valuable carriers that can improve the pharmaceutical phase, pharmacokinetics and pharmacodynamics of well-known drugs. D-galactose is a simple, naturally occurring monosaccharide sugar that has been extensively studied for use as a carrier and has proven to be valuable in this role. With the aim of validating the galactose-prodrug approach, we have investigated the galactosylated prodru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Importantly, galactos-6 ′ -yl ester prodrugs have demonstrated their utility in enhancing cell permeability and improving the pharmacokinetic properties of various drugs, thereby significantly reducing the occurrence of adverse effects while maintaining the efficacy of the parent drugs. In another study published by the same group in 2021, the pharmacological and toxicological profiles of these galactosylated prodrugs were reported to be superior to those of the parent drugs, with a significant reduction in ulcerogenicity [25].…”
Section: Galactose Conjugated Directly To the Parent Drugmentioning
confidence: 98%
See 1 more Smart Citation
“…Importantly, galactos-6 ′ -yl ester prodrugs have demonstrated their utility in enhancing cell permeability and improving the pharmacokinetic properties of various drugs, thereby significantly reducing the occurrence of adverse effects while maintaining the efficacy of the parent drugs. In another study published by the same group in 2021, the pharmacological and toxicological profiles of these galactosylated prodrugs were reported to be superior to those of the parent drugs, with a significant reduction in ulcerogenicity [25].…”
Section: Galactose Conjugated Directly To the Parent Drugmentioning
confidence: 98%
“…In another study published by the same group in 2021, the pharmacological and toxicological profiles of these galactosylated prodrugs were reported to be superior to those of the parent drugs, with a significant reduction in ulcerogenicity [ 25 ].…”
Section: Galactose For Drug Deliverymentioning
confidence: 99%
“…The microsomal stability results showed that the compound was minimally cleared % aGal A activity The AGAL molecule showed a LogD value of −0.43. The AGAL molecule has multiple hydroxyl groups contributing to lower lipophilicity, but because of its sugar-like structure it is expected to have improved solubility and cell permeability similar to [ 18 F]FDG and other galactosylated prodrugs [9,10].…”
Section: In Vitro Evaluation Of Agalmentioning
confidence: 99%
“…The majority of NSAID moieties are chemically made up of carboxylic functional groups, which may be one of the causes of mucosal membranes' direct injury. The ester, amides, amine, and anhydride derivatives completely mask the carboxylic groups and decrease the main direct effect of gastrointestinal (GI) ulceration and irritation [11]. Recently, Dana Ameen et al has been paying special attention to the diclofenac derivatives which exhibited no toxicity, and the preservation of stomach wall mucus may be the cause of gastroprotective effect [12].…”
Section: Introductionmentioning
confidence: 99%
“…Docking of Anthranilic acid derivatives (compounds[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] …”
mentioning
confidence: 99%